Hans Sachs. - Bibliographisches Institut (Hildburghausen) (Hildburghausen : Bibliographisches Institut in Hildburghausen, 1850)
Portret muškarca.
Dolje sredina ispod prikaza otisnuto: HANS SACHS // EIGENTHUM & VERLAG DES BIBL. INSTITUTS IN HILDBURGHAUSEN.; g.l. iznad prikaza otisnuto: NEVES CONVERS.LEXIC; g.d. iznad prikaza otisnuto: N.96.
Digitalna reprodukcija
Keywords: Nadorezi; Portreti